MEMILIH UNTUK MENJADI DEWASA: PEMANTAPAN PENDIDIKAN AGAMA KRISTEN - Rian Efendi Marbun; Redopri Ramayana Saragih; Morika Situmorang; Rahul Gabriel Hutabarat; Naomi Hotma Tiur Hutapea; Damayanti Nababan (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this study is to provide an understanding of the importance of the role of students in fostering adults in Marbun Toruan Village, Baktiraja District. The method used in this study is a qualitative research method. The result of this research is that in student service, students have a very important task in fostering adults, namely by conveying Christian religious education to adults by providing an understanding of adult human maturation. Therefore, with this very important task, students must be equipped with knowledge and skills in managing maturity.